2023
DOI: 10.3390/jcm12082909
|View full text |Cite
|
Sign up to set email alerts
|

Visual Prognostic Factors in Eyes with Subretinal Fluid Associated with Branch Retinal Vein Occlusion

Abstract: We investigated whether foveal ellipsoid zone (EZ) status affects visual prognosis in eyes with subretinal fluid (SRF) associated with branch retinal vein occlusion (BRVO). We included 38 eyes retrospectively and classified those with or without a continuous EZ on the SRF of the central foveola on the vertical optical coherence tomography (OCT) image at the initial visit as intact (n = 26) and disruptive EZ (n = 12) groups, respectively. In addition, we classified the intact EZ eyes into clear (n = 15) and blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Changes in the outer retina, such as in the photoreceptors, the external limiting membrane (ELM), or the ellipsoid zone (EZ), are strongly correlated with visual acuity (VA) in BRVO [5,6]. Some researchers reported that retinal ganglion cell (RGC) neurons are vulnerable to microvascular ischemia in diabetic retinopathy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the outer retina, such as in the photoreceptors, the external limiting membrane (ELM), or the ellipsoid zone (EZ), are strongly correlated with visual acuity (VA) in BRVO [5,6]. Some researchers reported that retinal ganglion cell (RGC) neurons are vulnerable to microvascular ischemia in diabetic retinopathy [7].…”
Section: Introductionmentioning
confidence: 99%